2019
DOI: 10.1111/1744-7941.12232
|View full text |Cite
|
Sign up to set email alerts
|

Temporary employment and voice behavior: the role of self‐efficacy and political savvy

Abstract: This study examines whether and how different employment arrangements (temporary versus regular employment) may affect employees' voice behaviors (promotive and prohibitive voice). Using a twowave panel design, we collected data from a sample of 355 employees from 66 teams in four Chinese organizations. The results show that temporary employees engage in fewer promotive voice behaviors than their regular counterparts, but there is no difference between the two groups when it comes to prohibitive voice. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
(139 reference statements)
0
25
1
Order By: Relevance
“…This means that subordinates' PsyCap may play a mediating role in the relationship between leader humility and subordinates' OCB/withdrawal behavior. First, several previous studies support the promoting effect of positive PsyCap on employees' extra-role behaviors [10,41,42,[46][47][48]. For example, Qian et al [46] found that employees with higher self-efficacy are less reluctant to speak up; Norman et al's [10] research demonstrated that positive PsyCap can promote employees to engage in more OCB and fewer deviance behaviors; and Avey et al's [48] meta-analysis supported the idea that PsyCap is positively related to desirable OCB behaviors, and negatively related to undesirable behaviors (turnover and deviance).…”
Section: The Mediating Role Of Subordinates' Psycapmentioning
confidence: 82%
See 1 more Smart Citation
“…This means that subordinates' PsyCap may play a mediating role in the relationship between leader humility and subordinates' OCB/withdrawal behavior. First, several previous studies support the promoting effect of positive PsyCap on employees' extra-role behaviors [10,41,42,[46][47][48]. For example, Qian et al [46] found that employees with higher self-efficacy are less reluctant to speak up; Norman et al's [10] research demonstrated that positive PsyCap can promote employees to engage in more OCB and fewer deviance behaviors; and Avey et al's [48] meta-analysis supported the idea that PsyCap is positively related to desirable OCB behaviors, and negatively related to undesirable behaviors (turnover and deviance).…”
Section: The Mediating Role Of Subordinates' Psycapmentioning
confidence: 82%
“…First, several previous studies support the promoting effect of positive PsyCap on employees' extra-role behaviors [10,41,42,[46][47][48]. For example, Qian et al [46] found that employees with higher self-efficacy are less reluctant to speak up; Norman et al's [10] research demonstrated that positive PsyCap can promote employees to engage in more OCB and fewer deviance behaviors; and Avey et al's [48] meta-analysis supported the idea that PsyCap is positively related to desirable OCB behaviors, and negatively related to undesirable behaviors (turnover and deviance). Consistent with these arguments, we propose the idea that subordinates' perceptions of leader humility may create positive work conditions necessary for subordinates' PsyCap to flourish, which, in turn, will promote subordinates to engage in more OCB [10,48] and fewer withdrawal behaviors [48].…”
Section: The Mediating Role Of Subordinates' Psycapmentioning
confidence: 82%
“…The proportion of project work in advanced economies equates to roughly a third of all business activities and 22% of the world's gross domestic product (Schoper, Wald, Ingason, & Fridgeirsson, 2018) in the fields of construction, defence, aerospace, and engineering and expanding into sectors such as power, pharmaceuticals, Information & Communications Technology, Research & Development, art/culture and creative industries, and service industries (Lundin et al, 2015). The normalisation of temporary work modes creates new employment relationships and changes the design of human resource management (HRM) systems and processes as emphasised in several publications in HRM journals (e.g., Bredin & Söderlund, 2007, 2011; Bredin & Söderlund, 2011; Qian, Li, Song, & Wang, 2019).
…”
Section: Introductionmentioning
confidence: 99%
“…Yet, PBOs face a challenge in this area because they do not have integrative coordination systems for employee voice (Matthews, Stanley, & Davidson, 2018). Studies examine aspects of voice in project settings in a disconnected manner (e.g., Dainty, Raidén, & Neale, 2009; Ekrot, Rank, & Gemünden, 2016; Gemünden, Lehner, & Kock, 2018; Kaufmann, Kock, & Gemünden, 2020; Liang, Shu, & Farh, 2019; Qian et al, 2019) or indirectly study voice (e.g., Aaltonen, 2013; D'Armagnac, 2015; Keegan & Den Hartog, 2018; Love, Teo, Davidson, Cumming, & Morrison, 2016). However, it is our view that the study of voice in PBOs is important for the following four challenges that PBOs face.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation